Pengaruh Model Pembelajaran Inkuiri Dan Creative Problem Solving Terhadap Hasil Belajar Siswa MTS Medan Tembung - Sari Fatmawati; Indayana Febriani Tanjung; Khairuna Khairuna (Universitas Lampung, 2022)
This study aims to determine the effect of the inquiry learning model and the creative problem-solving learning model on student learning outcomes. This research was conducted at MTs Madinatussalam Tembung for the academic year 2020/2021. The research method is quasi-experimental. The sample used in the study was 60 students, the sampling in this study was simple random sampling. The instrument in the study used a pretest and posttest. Based on the results of the research, the results of hypothesis testing on the results of the Inquiry class hypothesis test. From the table above, the value of t(count )= 8,594 and the value of t_(table )= 2.0243 so that t_(count)t_(table) which is therefore Ho is rejected. Ha accepted. Based on the results of hypothesis testing, there is an influence of the inquiry learning model. The results of the hypothesis test for the Creative Problem-Solving class. From the table above, the value of t(count )= 8, 683 and the value of t_(table )= 2.0243 so that t_(count )t_(table ) which means that Ho is rejected, Ha is accepted. Based on the results of hypothesis testing, there is an influence of the Inquiry learning model and Creative Problem-Solving learning model on student learning outcomes at MTs Madinatussalam Medan Tembung.Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran inkuiri dan model pembelajaran creative problem solving terhadap hasil belajar siswa. Penelitian ini dilaksanakan di MTs Madinatussalam Tembung tahun ajaran 2020/2021. Metode penelitian ini adalah eksperimen semu. Sampel yang digunakan dalam penelitian ini adalah 60 siswa, pengambilan sampel dalam penelitian ini adalah simple random sampling. Instrumen dalam penelitian ini menggunakan pretest dan posttest. Berdasarkan hasil penelitian, hasil pengujian hipotesis pada hasil uji hipotesis kelas Inkuiri. Dari tabel diatas diperoleh nilai t_(hitung )= 8,594 dan nilai t_(tabel )= 2,0243 sehingga t_(hitung)t_(tabel) maka Ho ditolak. Ha diterima. Berdasarkan hasil pengujian hipotesis terdapat pengaruh model pembelajaran inkuiri. Hasil uji hipotesis untuk kelas Creative Problem Solving. Dari tabel diatas diperoleh nilai t_(hitung )= 8,683 dan nilai t_(tabel )= 2,0243 sehingga t_(hitung )t_(tabel ) yang berarti Ho ditolak, Ha diterima. Berdasarkan hasil pengujian hipotesis, terdapat pengaruh model pembelajaran Inquiry dan model pembelajaran Creative Problem Solving terhadap hasil belajar siswa di MTs Madinatussalam Medan Tembung.Kata kunci: inkuiri, hasil belajar, pemecahan masalah secara kreatif DOI: http://dx.doi.org/10.23960/jbt.v10i2.24329